A systematic review and meta-analysis of the efficacy and safety of the interleukin (IL)-12/23 and IL-17 inhibitors ustekinumab, secukinumab, ixekizumab, brodalumab, guselkumab and tildrakizumab for the treatment of moderate to severe plaque psoriasis. (18th August 2018) - Bilal, Jawad; Berlinberg, Adam; Bhattacharjee, Sandipan; Trost, Jaren; Riaz, Irbaz Bin; Kurtzman, Drew J. B.
Abstract: Objective: To systematically analyze the efficacy and safety of interleukin (IL)-12/23, IL-17, and selective IL-23 inhibitors in moderate to severe plaque psoriasis. Methods and results: Twenty-four randomized placebo-controlled trials were included. Compared to placebo, risk ratios (RR) of achieving PASI-75 and PGA/IGA 0/1 respectively were 20.20 (95% CI 13.82–29.54, p  < .00001) and 14.55 (10.42–20.31, p  < .00001) for ustekinumab 90 mg, 13.75 (8.49–22.28, p  < .00001) and 9.81 (5.70–16.89, p  < .00001) for ustekinumab 45 mg, 17.65 (12.38–25.17, p  < .00001) and 26.13 (16.05–42.53, p  < .00001) for secukinumab 300 mg, 15.36 (10.76–21.94, p  < .00001) and 20.91 (12.82–34.13, p  < .00001) for secukinumab 150 mg, 18.22 (10.63–31.23, p  < .000001) and 18.82 (10.36–34.16, p  < .00001) for ixekizumab 80 mg every 4 weeks, 19.83 (11.07–35.52, p  < .00001) and 20.41 (11.01–37.81, p  < .00001) for ixekizumab 80 mg every 2 weeks, 14.79 (9.86–22.16, p  < .00001) and 21.93 (15.52–31.01, p  < .00001) for brodalumab 210 mg, 11.55 (7.77–17.18, p  < .00001) and 16.59 (11.72–23.49, p  < .00001) for brodalumab 140 mg, 12.40 (8.87–17.34, p  < .00001) and 10.84 (7.91–14.85, p  < .00001) for guselkumab 100 mg, 11.45 (7.45–17.58, p  < .00001) and 10.97 (6.44–18.69, p  < .00001) for tildrakizumab 200 mg, 11.02 (7.17–16.93, p  < .00001) and 10.03 (6.45–15.59, p  < .00001) for tildrakizumab 100 mg. Similar outcomes were seen for PASI-90. Safety was satisfactory for each therapy at any dose, but a slightly increased risk of withdrawal due to toxicity was observed in individuals receiving ixekizumab compared to placebo. Conclusion: Ustekinumab, secukinumab, ixekizumab, brodalumab, guselkumab, and tildrakizumab were highly efficacious and generally well-tolerated when used as treatments for moderate to severe plaque psoriasis.